2021
DOI: 10.1590/acb360403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rehmannia glutinosa polysaccharides on bone tissue structure and skeletal muscle atrophy in rats with disuse

Abstract: To study effects of Rehmannia glutinosa polysaccharides (RGP) on bone tissue structure and skeletal muscle atrophy in rats with disuse. Methods: A rat model of disuse osteoporosis combined with muscle atrophy was established by removing the bilateral ovaries of rats and fixing their hind limbs for a long time. Forty SD rats were administered intragastrically for 12 weeks. The bone histomorphometry parameters and the level of oxidative stress were measured. In addition, the changes of muscle atrophy F-box (MAFb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…[18] It also plays an antioxidative role in improving the bone structure of osteoporosis rats by improving muscle atrophy. [19] The components of the BHDH Decoction were identified using HERB. At present, most studies take OB ≥ 30% and DL ≥ 0.18 as the criteria for screening ingredients, which is not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…[18] It also plays an antioxidative role in improving the bone structure of osteoporosis rats by improving muscle atrophy. [19] The components of the BHDH Decoction were identified using HERB. At present, most studies take OB ≥ 30% and DL ≥ 0.18 as the criteria for screening ingredients, which is not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…Disuse-induced osteoporosis (DIO), which is a type of secondary osteoporosis with presently unsatisfactory treatment options, is a common complication caused by the lack, or disuse, of mechanical loading or systemic immobilization and constitutes a state of bone loss ( Yang et al., 2020 ; Rolvien and Amling, 2022 ). Currently, drug therapy remains the primary treatment for osteoporosis ( Ou et al., 2021 ). However, the long-term use of these drugs can lead to serious complications, including kidney damage, venous thrombosis, and an increased risk of developing tumors ( Ou et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, drug therapy remains the primary treatment for osteoporosis ( Ou et al., 2021 ). However, the long-term use of these drugs can lead to serious complications, including kidney damage, venous thrombosis, and an increased risk of developing tumors ( Ou et al., 2021 ). Thus, more effective, safe, and novel treatment strategies are urgently required for DIO.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that it has anti-inflammatory and antioxidative stress effects, enhances immunity and protects cardiovascular function. 20,21 However, there are no studies on the protective effects of RGP on the intestine; therefore, we aimed to investigate the protective effects of RGP on the intestine of dextran sodium sulfate IBD mice and the underlying mechanisms, including altering the intestinal microbiota, thereby repairing intestinal epithelial damage. To the best of our knowledge, the present study provides the first comprehensive intestinal evidence that RGP can effectively modulate gut microbiota and prebiotic integrative responses for the treatment of DSS-induced colitis.…”
Section: Introductionmentioning
confidence: 99%
“…Rehmannia glutinosa polysaccharide (RGP) is an important active component of the traditional Chinese herbal medicine rehmannia glutinosa, which has a wide range of pharmacological activities. Previous studies have shown that it has anti‐inflammatory and antioxidative stress effects, enhances immunity and protects cardiovascular function 20,21 . However, there are no studies on the protective effects of RGP on the intestine; therefore, we aimed to investigate the protective effects of RGP on the intestine of dextran sodium sulfate IBD mice and the underlying mechanisms, including altering the intestinal microbiota, thereby repairing intestinal epithelial damage.…”
Section: Introductionmentioning
confidence: 99%